O ensaio na crítica literária brasileira contemporânea - Maciel, Keila Mara de Souza Araújo (2017)
This thesis intends to understand the reasons that make the essay the most frequent form of writing in the Brazilian literary criticism of the 21st century, at a time when the critic reviews his performance. With this in mind, Michel Foucault's concepts of device and counter-device become a starting point for reflection, which allows us to recognize in the essay the possibility of new paths to rationality in the contemporary world, alongside literature. The study follows the course of the essay, which develops side by side with the process of formation of critical thinking from Michel de Montaigne, passing through the strong critical tradition of German Romanticism, rescued by Georg Lukács and Walter Benjamin, until finding, since the second half of the twentieth century, in Theodor Adorno and Roland Barthes even more complex developments for the critical-philosophical essay. From these premises, the work of analysis goes to meet authors who explore the possibilities of the essay in their works, making inseparable, in many moments, literary text and critical text. The reflections turn to the theoretical and critical studies of literature, with emphasis on the texts of Antonio Candido, Roberto Schwarz, Silviano Santiago, João Cezar de Castro Rocha, Alberto Pucheu and Nuno Ramos, with the aim of bringing to light the contributions of the essay for literary studies in Brazil. Especially with regard to the insertion of the aesthetic resources of the language to the procedures of critical analysis, even approaching the extremes of the constant fluctuation between the objective order and the subjective order of the literary writing, emphasizing the authorial presence and the ethical positioning before the themes which the authors referred to in this thesis propose to think.